PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA KARYAWAN (STUDI KASUS PADA KARYAWAN HOTEL DYAN GRAHA PEKANBARU) - Putri, Ismelda; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of Work Environment and Job Characteristics on Employee Job Satisfaction at Hotel DyanGrahaPekanbaru. Where two independent variables and one bound are proposed, namely the work environment and job characteristics as independent variables and job satisfaction as the dependent variable.              The research method was descriptive and using the SPSS 23 program, where the sample used was employees of DyanGrahaPekanbaru Hotel with respondents as many as 54 people. For sampling techniques using the census method.Data collection techniques through questionnaires and interviews. The results of the analysis use the validity test.  Determination test, simple linear regression test, multiple linear regression test, t test, and test so that it can be seen that the work environment has a significant effect on employee job satisfaction at DyanGrahaPekanbaru Hotel, job characteristics have a significant effect on employee job satisfaction at DyanGrahaPekanbaru Hotel, and the work environment and job characteristics have a significant effect on employee job satisfaction at Hotel DyanGrahaPekanbaru.   Keywords: Work Environment, Job Characteristics and Job Satisfaction